Trends in in-utero transfer: royal wolverhampton hospitals NHS trust 2007 to 2010. (7th June 2011) - Vanner, T; Rooney, M; Blackburn, S
Abstract : An audit of In-utero transfers into RWHT was undertaken in 2007. Following this an IUT form was developed by the Staffordshire, Shropshire and Black Country Maternity Network to aid communication between units. A process of follow-up to determine the outcome and an anonymous database held by the SSBC commenced in April 2009 with RWHT, a Level 3 designated unit being the first unit to submit data. Trends in IUT into RWHT since 2007 will be presented. Interim analysis demonstrates that there has been a sustained reduction in the number of IUTs into the unit and the proportion of transfers that are from within the SSBC network has increased from 29% to over 45%, with a reduction from the adjacent network and other regions. Transfers because of the level of neonatal care required rather than capacity issues has remained at 40%. The percentage giving birth as a result of the transfer is unchanged (41%). Where the indication for transfer was premature labour over 70% were discharged home undelivered in 2007 and 2009. This reduced to 58% in 2010. By 2010 fetal fibronectin or similar testing was available in all transferring units. Despite Network agreed guidelines on IUT, women with a negative FFN test were transferred and all (6 in 2010) were discharged home undelivered following the IUT. Establishment of perinatal networks has led to considerable improvement in the coordination of IUT. There is the potential for this to improve further with stricter adherence to network agreed guidelines.